2022
DOI: 10.1186/s13052-022-01285-8
|View full text |Cite
|
Sign up to set email alerts
|

A height-weight formula to measure body fat in childhood obesity

Abstract: Background The assessment of body composition is central in diagnosis and treatment of paediatric obesity, but a criterion method is not feasible in clinical practice. Even the use of bioelectrical impedance analysis (BIA) is limited in children. Body mass index (BMI) Z-score is frequently used as a proxy index of body composition, but it does not discriminate between fat mass and fat-free mass. We aimed to assess the extent to which fat mass and percentage of body fat estimated by a height-wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Considering additional factors beyond numerical thresholds is crucial for accurately evaluating health risks and guiding healthcare interventions in older adults [ 31 ]. BMI and z-scores in children are more complex and are not reviewed here [ 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering additional factors beyond numerical thresholds is crucial for accurately evaluating health risks and guiding healthcare interventions in older adults [ 31 ]. BMI and z-scores in children are more complex and are not reviewed here [ 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…Obesity status can be subcategorized further to capture more or less severe BMI variance [ 3 ]. BMI is relatively simple to measure in adults [ 4 , 5 , 6 , 7 , 8 , 9 ] and functionally sums a variety of complex body indicators. (Interpreting BMI in children is more complex and is not reviewed here.)…”
Section: Introductionmentioning
confidence: 99%
“…A functional study showed that the Val642Leu mutant exhibited significantly higher enzymatic activity and EO than the wild-type protein [ 19 ]. Moreover, a study by Lanzani et al reported that hypertensive subjects who were homozygous for the A allele displayed a more pronounced reduction in blood pressure after consuming a low-salt diet compared to AC and CC subjects [ 24 ]. Nevertheless, these findings have not been verified in pediatric cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…The tri-ponderal mass index (TMI) was calculated as weight (kg)/height 3 (m 3 ) [ 22 ]. A height–weight formula proposed by Hudda et al was calculated as previously described [ 23 , 24 ]. Blood pressure was measured three times, and the average value of the measurements was recorded.…”
Section: Methodsmentioning
confidence: 99%